Solve the following=
(-3)×1×(-2)×(-2)
Answers
Answered by
0
Step-by-step explanation:
hope this helps have a nice day dear.
Attachments:
![](https://hi-static.z-dn.net/files/d65/0046aa36ce6095e1508d78cf307c672c.jpg)
Answered by
0
We have to solve this step by step.
-3 × 1 = -3
-3 × -2 = 6
6 × -2 = -12
So -3×1×-2×-2 = -12
Hope it helps and plsss mark Brainliest
Similar questions
English,
6 months ago
History,
6 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Hindi,
1 year ago
Social Sciences,
1 year ago